2019
DOI: 10.15386/mpr-1195
|View full text |Cite
|
Sign up to set email alerts
|

Miniplate removal in operated cases of maxillofacial region in a dental institute in Rajasthan, India

Abstract: BackgroundThe long term management of miniplate fixation osteosynthesis remains debatable and controversial with few authors advocating routine removal of the miniplates after 3–6 months of placement, while others recommend retention of the miniplates unless their removal is clinically indicated.ObjectiveThe aim was to study the incidence, indications, time gap, role of metallic composition and site of removal of miniplates in operated cases of maxillofacial region over a two-year period.MethodsPatients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…A few studies reported that the majority of the patients underwent hardware removal during the first year, while a few studies reported that most patients required hardware removal within 6 months following surgery. [ 13 16 17 ] It is advocated that the hardware removal is easier within 6 months following surgery and with an increase in time, it would become difficult to remove the hardware, particularly in young patients in whom the hardware is often covered by bone. [ 16 ] A previous study revealed that a residual granulation tissue forms around long-standing hardware which becomes necrotic, leading to long-standing inflammation and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported that the majority of the patients underwent hardware removal during the first year, while a few studies reported that most patients required hardware removal within 6 months following surgery. [ 13 16 17 ] It is advocated that the hardware removal is easier within 6 months following surgery and with an increase in time, it would become difficult to remove the hardware, particularly in young patients in whom the hardware is often covered by bone. [ 16 ] A previous study revealed that a residual granulation tissue forms around long-standing hardware which becomes necrotic, leading to long-standing inflammation and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Miniplate removal should primarily address miniplate-related symptoms. While some authors advocate routinely removing miniplates to avert interference with jaw function and osteoporosis, most studies suggest removal only when symptoms manifest and discourage the routine removal of asymptomatic miniplates [12,[41][42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Removal of miniplates has been a controversial topic since its introduction and hasn't ceased to be so. The authors who favor miniplate retention argue the potential risk caused by a second surgery under general anesthesia and profess asymptomatic removal of miniplates as uncalled for and pose more harm than favor (Khandelwal et al, 2019). This argument has been strengthened by the use of biocompatible and osseointegrative mini plates made up of titanium (Park et al, 2016).…”
Section: B Computed Only For a 2x2 Tablementioning
confidence: 99%